The relationship between executive functioning and self‐regulated learning in Australian children. (9th July 2021) - Davis, Helen; Valcan, Debora Similieana; Pino‐Pasternak, Deborah
Abstract : Executive functioning (EF) and self‐regulated learning (SRL) are established predictors of academic achievement, both concurrent and future. Although it has been theorized that EF development enables SRL in early childhood, this directional model remains empirically untested against plausible alternatives. Thus, this study investigated the longitudinal relations between children's EF and SRL during the transition from kindergarten to Year 1 in an Australian sample to determine the direction and strength of the association between EF and SRL. We compared four directional models and also tested whether EF and SRL can be construed as manifestations of a common factor. Children's EF was assessed using a battery of tasks tapping working memory, inhibition, and shifting, and their SRL was assessed by teachers using the Checklist of Independent Learning Development. Cross‐lagged structural equation modelling analyses were conducted on a longitudinal dataset of 176 children at the end of kindergarten (age M = 5 years, 8 months; SD = 4.02 months), and 1 year later (age M = 6 years, 5 months; SD = 3.65 months). EF predicted SRL longitudinally (β= .58, controlling for kindergarten SRL), consistent with common assumptions, whereas SRL did not predict EF. However, the common factor model also fit the data very well. We concluded that EF and SRL are indeed related concurrently and longitudinally but that further evidence is needed to disambiguate whether EF is best understood as a necessary antecedent of SRL development in early childhood, or whether they reflect the same general construct.